2014
DOI: 10.15389/agrobiology.2014.6.107eng
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Lipid Oxidation and Reproductive Health of Cows

Abstract: A b s t r a c tFree radical lipid oxidation is currently considered as one of the dominant metabolic processes of physiological system functional activity. When it goes beyond regulated limits it is considered as an inductor of free radical pathology oxidative stress. In the conditions of a big dairy cattle breeding farm (Voronezh Province), specialized in Red-and-White breed, the functioning peculiarities of the peroxidation system lipid-oxidant defense in cows at the normal course of gestation and at gestosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…У свиноматок обеих групп установлено существенное увеличение содержания NO• в 10,4 и 11,0 раз, что связано с ростом активности NO-синтаз и продукции оксида азота для расслабления гладких мышц матки, торможения сокращения матки в течение беременности и снижения тонуса цервикального канала [8]. Протекторное действие обеспечивается способностью NO• увеличивать активность антиоксидантных ферментов, а также взаимодействовать с супероксиданион -радикалом и обеспечивать детоксикацию потенциально опасных активных форм кислорода [6].…”
Section: показателиunclassified
“…У свиноматок обеих групп установлено существенное увеличение содержания NO• в 10,4 и 11,0 раз, что связано с ростом активности NO-синтаз и продукции оксида азота для расслабления гладких мышц матки, торможения сокращения матки в течение беременности и снижения тонуса цервикального канала [8]. Протекторное действие обеспечивается способностью NO• увеличивать активность антиоксидантных ферментов, а также взаимодействовать с супероксиданион -радикалом и обеспечивать детоксикацию потенциально опасных активных форм кислорода [6].…”
Section: показателиunclassified
“…In addition to a sufficient iodine intake into the body for the production of thyroid hormones, it is important to ensure an adequate selenium intake from the feed. According to the number of studies, it has been found that pathological conditions of the reproductive system develop against the background of an increased level of oxidative stress, aggravated by a lack of micronutrients included in a structure of antioxidant enzymes (Awadeh et al, 1998;Safonov et al, 2008, Safonov et al, 2014, Kireev et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…After introducing carrots into the diet of cows, Japanese scientists noted that "feeding carrots improved the IgG1 concentration in the plasma of the cows during parturition [19]." Therefore, more biochemical and hematological studies of cattle blood are needed [20][21][22][23][24]. The biochemical and hematological studies of cow blood are widely used for predicting or diagnosing antepartum and postpartum metabolic disorders in cows [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%